2022
DOI: 10.3390/agronomy12020250
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Mapping for Seed Weight in Soybean with Black Seed Coats and Green Cotyledons

Abstract: The yield of soybean (Glycine max (L.) Merr.) is based on several components, such as the number of plants per unit area, pod number per plant, number of nodes, and seed weight. Additionally, the hundred-seed weight (HSW) is an important component affecting soybean yield. The HSW trait can determine soy products meant for human consumption. In this study, we conducted genome-wide association studies with 470 accessions of black seed coats with green cotyledons and applied an online tool with publicly available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Their study found two stable seed yield QTNs on chromosomes 9 and 17 detected consistently in three environments. In addition, using 6K SNP markers and 470 soybean accessions, 14 QTNs were identified for seed yield-related traits on 6 different chromosomes ( Jo et al., 2022 ). Similar studies with significant effects on seed yield traits in a selected population of soybean germplasm were reported ( Zhang et al., 2016a ; Yan et al., 2017 ; Copley et al., 2018 ; Li et al., 2019a ; Li et al., 2019c ).…”
Section: Molecular Genetic and Genomics Basis Of Soybean Yield Traitsmentioning
confidence: 99%
“…Their study found two stable seed yield QTNs on chromosomes 9 and 17 detected consistently in three environments. In addition, using 6K SNP markers and 470 soybean accessions, 14 QTNs were identified for seed yield-related traits on 6 different chromosomes ( Jo et al., 2022 ). Similar studies with significant effects on seed yield traits in a selected population of soybean germplasm were reported ( Zhang et al., 2016a ; Yan et al., 2017 ; Copley et al., 2018 ; Li et al., 2019a ; Li et al., 2019c ).…”
Section: Molecular Genetic and Genomics Basis Of Soybean Yield Traitsmentioning
confidence: 99%
“…Soybean, known as the 'meat of the field', is one of the world's most economically and nutritionally important crops, containing 40% protein, 20% oil [1], and isoflavones; it dominates global oilseed production, and it is one of the world's most important protein sources and also the primary protein supply in animal feed [2]. According to the growth rate, the world's population is expected to reach 9.8 billion in 2050 and 11.2 billion in 2100.…”
Section: Introductionmentioning
confidence: 99%